Endocuff assisted colonoscopy significantly increases sessile serrated adenoma detection in veterans - Baek, Michael D. (J Gastrointest Oncol, 2017)
BACKGROUND: Colorectal cancer (CRC) is the second most common cause of cancer related deaths in the United States. Colonoscopy is the gold standard for the detection of CRC. There are many colonoscopy quality measures and among these the adenoma detection rate (ADR) has demonstrated a significant impact in reducing mortality from CRC. The primary aim of our study was to compare ADR and distribution of polyp type in patients undergoing Endocuff-assisted colonoscopy (EAC) versus standard colonoscopy (SC) in a VA system. METHODS: Retrospective data was collected from 496 patients who underwent routine screening, surveillance and diagnostic colonoscopies either via SC from January 6, 2014 through March 12, 2014 or EAC from September 24, 2014 through February 19, 2015. A total of 54 patients were excluded based on a personal history of CRC and prior resection, incomplete colonoscopy due to poor bowel preparation, and removal or loss of Endocuff (EC). Primary outcomes measured and compared were ADR and types of polyps found. RESULTS: The overall ADR in the EAC group was higher at 59.91% versus 50.66% for SC, accounting for a 9% increase (P=0.0508). EAC was able to detect a total of 59 sessile serrated adenoma/polyps (SSA/Ps) compared to SC only detecting 8 (P≤0.0001). There was a significant increase in the SSA/P detection rate with EAC at 15% versus 3% in the SC group (P≤0.0001). CONCLUSIONS: EAC significantly increases the detection of SSA/P and has shown a trend in improving ADR in our veteran population.